Pengaruh Kualitas Sistem, Layanan, Pemasaran Relasional terhadap Loyalitas melalui Kepuasan Pengguna - Winda Fuji Lestari Toni (Penerbit Goodwood, 2025)
Purpose: This study analyzes how system quality, service quality, and relational marketing influence user satisfaction and loyalty in using the BSB Mobile app at Bank Sumsel Babel Syariah Palembang. Methodology/approach: A quantitative study with 266 purposively selected BSB Mobile users was analyzed using PLS-SEM via SmartPLS, with data collected through an online survey and demographics analyzed using SPSS. Results/findings: System quality, service quality, and relational marketing positively impact user satisfaction, which in turn strengthens user loyalty to the BSB Mobile app. User satisfaction acts as a key mediator, highlighting the importance of reliable systems, quality service, and strong customer relationships in mobile banking loyalty. Conclusion: The study confirms that improving system quality, service quality, and relational marketing enhances user satisfaction, which subsequently fosters user loyalty to BSB Mobile. These variables interact synergistically in shaping positive user experiences. Limitations: This study is only focus on system quality, service quality and relationship marketing on user loyalty with user satisfaction as intervening variable at Bank Sumsel Babel Syariah Palembang Branch. Contribution: The study provides empirical insights into how banks can strategically improve mobile banking performance by focusing on system reliability, service excellence, and relational engagement to strengthen customer loyalty.